Does disaster-related relocation impact mental health via changes in group participation among older adults? Causal mediation analysis of a pre-post disaster study of the 2016 Kumamoto earthquake - Yoko Matsuoka; Maho Haseda; Mariko Kanamori; Koryu Sato; Airi Amemiya; Toshiyuki Ojima; Daisuke Takagi; Masamichi Hanazato; Naoki Kondo (BMC, 2023)
Abstract Background Disaster-related relocation is associated with depression and post-traumatic stress disorder, especially in older adults. Disaster-related relocation often deprives survivors of opportunities for social group participation, potentially deteriorating their mental health. On the contrary, the relocation could also be an opportunity for optimizing social relationships, ending/reducing unwanted participation. This study examined the potential mediation effects of changing participation for the link of disaster-related relocation to mental health. Methods We analyzed a pre-post disaster dataset of functionally independent older adults from the Japan Gerontological Evaluation Study. Following the 2013 survey, a follow-up survey was conducted seven months after the 2016 Kumamoto earthquake (n = 828). Results The causal mediation analyses indicated that compared to no relocation, the relative risk for experiencing major depressive episodes among those relocating to temporary housing was 3.79 [95% confidence interval: 1.70-6.64] (natural direct effect). By contrast, the relative risk for those renewing (either ceased or started) group participation was 0.60 [95% CI: 0.34-0.94] (natural indirect effect). Conclusions Optimization of social ties according to a renewal of group participation status might have protected older adults in temporary housing against depression.